Agriculture Initiatives and COP22: A step towards fighting climate change - Dinesh, Dhanush; Olesen, Asger S; Richards, M; Guizani, Sara; Andersen, S.P. (Nordisk Ministerråd, 2016)
Against the backdrop of population increase, changing dietary patterns, increased affluence and rising demands on land for the generation of biofuels, agricultural productivity is required to increase significantly in the coming years. This increase will take place in a context of constrained resources and a changing global climate requiring increased adaptive capacity and increased resilience of agricultural systems. At the same time, agricultural activities are contributing significantly to climate change, with agricultural production and the food supply chain being responsible for up to a third of total anthropogenic greenhouse gas (GHG) emissions.